Optimalizace velikosti terče a odhodové vzdálenosti při hodu na cíl pro dospělé osoby Optimisation of the size of a target and the throwing distance during a throw at a target for adults - Vojtěch Gajda (Acta Universitatis Palackianae Olomucensis. Gymnica, 2008)
Cílem studie je optimalizovat odhodovou vzdálenost a velikost terče jako východisko ke konstrukci testu přesnosti hodu na cíl tenisovým míčem. Optimální kombinace musí splňovat dvě podmínky – testovaný soubor dosáhne u konkrétní kombinace velikosti terče a odhodové vzdálenosti průměrné hodnoty počtu úspěšných zásahů terče z celkového počtu hodů a bude splňovat podmínku normálního rozdělení. Zkoumaný soubor tvořilo 79 mužů a 71 žen, studentů prvního ročníku oborů tělesná výchova a rekreologie Ostravské univerzity v Ostravě. Pro experiment byly zvoleny pro obě kategorie tři velikosti terče (0,5; 0,7; 0,9 m) a tři odhodové vzdálenosti (6, 10, 14 m pro muže a 4, 6, 8 m pro ženy) – celkem devět kombinací. Skóre experimentu tvoří počet úspěšných zásahů terče z desíti hodů v každé kombinaci velikosti terče a odhodové vzdálenosti. Pro řešení problematiky byly použity metody testování normality rozložení experimentálních dat (Kolmogorov-Smirnov), jednofaktorová analýza rozptylu (Scheffe) a základní statistické charakteristiky. Výzkum prokázal, že stanovené podmínky splňuje v kategorii mužů kombinace odhodové vzdálenosti a velikosti terče 10 m/0,7 m a v kategorii žen kombinace 6 m/0,7 m. The aim of the study is to optimise throwing distance and the size of a target as a basis for constructing a test of accuracy of a throw at a target, using a tennis ball. The optimal combination must fulfil two conditions – the tested group will achieve an average score of the count of successful hits out of all throws and using a specific combination of the throwing distance and the size of a target and it will fulfil the condition of normal distribution. The tested group consisted of 79 men and 71 women, students of the first year at the Ostrava University in Ostrava, majoring in the Physical Education and Recreation study fields. Three target sizes (0.5, 0.7 and 0.9 m) and three throwing distances (6, 10 and 14 m for men and 4, 6 and 8 m for women) were selected for both categories for the experiment, altogether nine combinations. The score of the experiment is formed by the count of successful hits of the target, out of ten throws, using each combination of the size of a target and the throwing distance. To solve the issue, the methods of testing the normal Gaussian distribution of data (Kolmogorov-Smirnov), the one way analysis of variance (Scheffe) and descriptive statistics have been used. The research confirmed that the determined conditions are fulfilled by the 10 m/0.7 m combination of the throwing distance and the size of a target for the men's category and the 6 m/0.7 m combination for the women's category.